Productivity of mini-cuttings of a hybrid clone of Eucalyptus urophylla x Eucalyptus pellita as a function of exposure time of mini-stumps to mini-tunnel - Rocha, Fabiana Miranda; Maravilha, Luiz Filipe; Titon, Miranda; de-Oliveira-Fernandes, Sula Janaína; Mendonça-Machado, Evandro Luiz; de-Souza-Martins, Nivaldo (Bosque (Valdivia), 2023)
With the implementation of the mini-cutting technique in Eucalyptus, several alternatives have emerged to improve structures for plant propagation, growth, and development. A technology recently applied in the propagation of eucalyptus in clonal mini-gardens is the mini-tunnel, which has shown promise in increasing mini-stump productivity and the rooting of mini-cuttings. The aim of this study was to evaluate the effect of exposure times for mini-stumps to mini-tunnel on the productivity of mini-cuttings from a hybrid clone of Eucalyptus urophylla x Eucalyptus pellita. Four exposure times were tested: 0 days (control), 15, 30, and 45 days. The total productivity and effective productivity of mini-cuttings per mini-stump were evaluated, as well as the levels of chlorophyll a, b, and total chlorophyll, height, leaf area, and dry mass of the mini-cuttings. The results showed that a 45-day exposure period of mini-stumps to the mini-tunnel resulted in increased mini-cutting productivity, greater height, higher chlorophyll content, smaller leaf area, and reduced dry biomass of the mini-cuttings. These findings offer advantages for managing clonal mini-gardens.